Understanding secondary injury - Borgens, Richard Ben; Liu-Snyder, Peishan (The Quarterly review of biology, 2012)
Secondary injury is a term applied to the destructive and self-propagating biological changes in cells and tissues that lead to their dysfunction or death over hours to weeks after the initial insult (the "primary injury"). In most contexts, the initial injury is usually mechanical. The more destructive phase of secondary injury is, however, more responsible for cell death and functional deficits. This subject is described and reviewed differently in the literature. To biomedical researchers, systemic and tissue-level changes such as hemorrhage, edema, and ischemia usually define this subject. To cell and molecular biologists, "secondary injury" refers to a series of predominately molecular events and an increasingly restricted set of aberrant biochemical pathways and products. These biochemical and ionic changes are seen to lead to death of the initially compromised cells and "healthy" cells nearby through necrosis or apoptosis. This latter process is called "bystander damage." These viewpoints have largely dominated the recent literature, especially in studies of the central nervous system (CNS), often without attempts to place the molecular events in the context of progressive systemic and tissue-level changes. Here we provide a more comprehensive and inclusive discussion of this topic.